2019
DOI: 10.3348/jksr.2019.80.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Renal Ultrasonography for Vesicoureteral Reflux in Infants and Children Aged Under 24 Months with Urinary Tract Infections

Abstract: Purpose To compare the diagnostic accuracies of renal ultrasonography (US) and voiding cystourethrography (VCUG) for vesicoureteral reflux (VUR). Materials and MethodsThis retrospective study included infants and children (< 24 months of age) with urinary tract infections who underwent renal US and VCUG. The incidences of decreased or increased renal size, increased renal parenchymal echogenicity, ureteral dilation, ureteral wall thickening, renal pelvic dilation, pelvic wall thickening, and accentuated pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In most of the previous studies, none of these parameters were not evaluated in US [13,17,18]. In some studies emphasizing the importance of US parameters other than APRPD (such as decreased renal size, increased renal parenchymal echogenicity and ureteral dilation), decreased renal size and ureter dilatation were found to be the most important parameters [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In most of the previous studies, none of these parameters were not evaluated in US [13,17,18]. In some studies emphasizing the importance of US parameters other than APRPD (such as decreased renal size, increased renal parenchymal echogenicity and ureteral dilation), decreased renal size and ureter dilatation were found to be the most important parameters [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the most important reason for the superiority of UTD sensitivity, PPV, and NPV over SFU was that the ureter dilation and parenchymal echogenicity increased the UTD degree even with a normal pelvicalyceal system. In many studies, these parameters are shown to increase the sensitivity and specificity of US detection for VUR [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%